Efek Inhibisi Senyawa Aktif Spoge Haliclona sp. terhadap Pertumbuhan Plasmodium falciparum Berdasarkan Studi In Slico - Wulandari, Ni Made Diah; Utami, Prawesty Diah; Sukmana, Judya (Syifa'Medika, 2025)
Malaria is still a problem in many places, caused by a parasite Plasmodium falciparum spreaded by mosquitoes. Haliclona sp. is a sea sponge that contains active compounds, some of which are Manzamine and Haliclonacyclamine A, and have antimalarial activity. This study aimed to find the potential effects of different active compounds on the sponge Haliclona sp. on the growth of Plasmodium falciparum based on in silico. This was an experimental study using in silico method. The materials were prepared and taken from the PubChem web, predicted the potential of compounds, predicted pathways using Discovery Studio version 21.1.1, molecular docking using Molegro virtual Docker 5.0, predicted ADME using SWISS ADME, and predicted toxicity via Protox web. The results showed that Haliclona sp. contained several active compounds, namely Manzamine and Haliclonacyclamine A. The study of the active compounds in Haliclona sp. showed that there was a link between the Plasmodium falciparum enzymes. The PfTK and PfDHODH enzymes are responsible for breaking down malaria parasites. In the ADME prediction analysis of the active compounds contained in Haliclona sp., Haliclonacyclamine A can meet Lipinski's criteria. The last test performed was a toxicity test where it was found that Haliclonacyclamine.